2015
DOI: 10.4172/2573-4598.1000101
|View full text |Cite
|
Sign up to set email alerts
|

The Dying and Those Who Care for Them

Abstract: The article reviews the loneliness of those on their deathbed, and the complex and demanding field of palliative care, noting the sources of the stresses and strains that the healthcare workers often encounter. It highlights the needs of patients, the reasons why they and/or their families may hamper palliative care, and mostly-what can be done to deal with, and better yet-prevent, palliative workers' burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Positive, sometimes transformative (Mota Vargas et al, 2016), experiences are reported by palliative care staff such as compassion satisfaction, an enhanced sense of spirituality, opportunity to live at present and be able to deeply reflect on the meaning and continuity of life (Sinclair, 2011). However, frequent exposure to suffering, death and dying, the complexity of caregiving activities at the end of life (Lindqvist et al, 2012), and the high levels of emotional labour involved in working with the dying (Funk et al, 2017; Rokach, 2015) constitute significant challenges.…”
Section: Work-related Stress and Coping In Palliative Care Staffmentioning
confidence: 99%
“…Positive, sometimes transformative (Mota Vargas et al, 2016), experiences are reported by palliative care staff such as compassion satisfaction, an enhanced sense of spirituality, opportunity to live at present and be able to deeply reflect on the meaning and continuity of life (Sinclair, 2011). However, frequent exposure to suffering, death and dying, the complexity of caregiving activities at the end of life (Lindqvist et al, 2012), and the high levels of emotional labour involved in working with the dying (Funk et al, 2017; Rokach, 2015) constitute significant challenges.…”
Section: Work-related Stress and Coping In Palliative Care Staffmentioning
confidence: 99%
“…Although estimates of prevalence vary, a notable number of hospice patients experience depression and anxiety, and there are grounds to think such conditions are underreported (Hayes et al, 2017; Irwin et al, 2008; Kozlov et al, 2019). In addition, loneliness and lack of relational connectedness impact hospice patients’ quality of life (Bale et al, 2016; Rokach, 2016; Sawyer et al, 2019; Untas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%